'It's a big ask when your job is to teach children to read, write and to count': the experiences of school staff in early help and child protection. (2nd January 2018) - Richards, Clare
Abstract: Considers the experiences of designated safeguarding staff in primary aged schools (4–11 years). The study used semi-structured interviews to explore with professionals their experiences of multi-agency working to safeguard children, of factors in making decisions around reporting concerns to statutory social work services and their role in delivering early help services in one region of the U.K. Professionals raised concerns about their understanding of decisions made by social workers, but nevertheless said that these decisions affected their future reporting of safeguarding concerns. Professionals raised concern about how current safeguarding processes triage concerns around neglect, and as the effect was cumulative, felt that it could be minimised or overlooked.